Presence and Effects of Pituitary Adenylate Cyclase Activating Polypeptide Under Physiological and Pathological Conditions in the Stomach - Reglodi, Dora; Illes, Anita; Opper, Balazs; Schafer, Eszter; Tamas, Andrea; Horvath, Gabriella (Frontiers in Endocrinology, 2018)
Pituitary adenylate cyclase activating polypeptide (PACAP) is a multifunctional neuropeptide with widespread occurrence throughout the body including the gastrointestinal system. In the small and large intestine, effects of PACAP on cell proliferation, secretion, motility, gut immunology and blood flow, as well as its importance in bowel inflammatory reactions and cancer development have been shown and reviewed earlier. However, no current review is available on the actions of PACAP in the stomach in spite of numerous data published on the gastric presence and actions of the peptide. Therefore, the aim of the present review is to summarize currently available data on the distribution and effects of PACAP in the stomach. We review data on the localization of PACAP and its receptors in the stomach wall of various mammalian and non-mammalian species, then we give an overview on PACAP’s effects on secretion of gastric acid and various hormones. Effects on cell proliferation, differentiation, blood flow and gastric motility are also reviewed. Finally, we outline PACAP’s involvement and changes in various pathological conditions, completed with recent experimental data on human gastritis and ulcer patients.